Conductive polymer dispersion and method for manufacturing conductive polymer dispersion, solid electrolytic capacitor, and method for manufacturing solid electrolytic capacitor

JP2025032011AActive Publication Date: 2025-03-07NIPPON CHEMI CON CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024232068
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-07
Estimated Expiration
2041-03-18

AI Technical Summary

Benefits of technology

【0019】 本発明によれば、導電性高分子分散液の酸性度が高いことに起因する封口体の劣化と静電容量の低下を抑制できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025032011000001_ABST
    Figure 2025032011000001_ABST
Patent Text Reader

Abstract

To provide a conductive polymer dispersion that is resistant to a decrease in capacitance while maintaining the effect of suppressing an increase in ESR of a solid electrolytic capacitor, a manufacturing method thereof, a solid electrolytic capacitor made from the conductive polymer dispersion, and a manufacturing method thereof.SOLUTION: A conductive polymer dispersion forms a solid electrolyte layer in a capacitor element. A manufacturing method of the conductive polymer dispersion includes a mixing step of mixing at least a solvent, a conductive polymer, and an alkaline component, and in the mixing step, both a volatile alkaline component and a non-volatile alkaline component are mixed into the conductive polymer dispersion as the alkaline component.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a conductive polymer dispersion in which a conductive polymer is dispersed, the conductive polymer dispersion, a solid electrolytic capacitor in which a solid electrolyte layer is formed from the conductive polymer dispersion, and a method for producing a solid electrolytic capacitor from the conductive polymer dispersion. [Background technology]

[0002] Electrolytic capacitors using valve metals such as tantalum or aluminum can achieve a small size and large capacity by expanding the surface area of ​​the dielectric by forming the valve metal as the anode electrode into a sintered body or etched foil, etc. In particular, solid electrolytic capacitors, in which a dielectric oxide film is covered with a solid electrolyte, are small in size, have a large capacity, and have a low equivalent series resistance, making them indispensable for miniaturizing electronic devices, improving their functionality, and reducing their costs.

[0003] Known examples of solid electrolytes include manganese dioxide and 7,7,8,8-tetracyanoquinodimethane (TCNQ) complexes. In recent years, conductive polymers derived from monomers with π-conjugated double bonds, such as poly(3,4-ethylenedioxythiophene) (PEDOT), which has a slow reaction rate and excellent adhesion to dielectric oxide films, have rapidly become popular as solid electrolytes. In conductive polymers, acid compounds such as polyanions are used as dopants during chemical oxidative polymerization or electrolytic oxidative polymerization, resulting in high conductivity.

[0004] However, compared to liquid-type electrolytic capacitors in which the capacitor element is impregnated with an electrolytic solution and does not have a solid electrolyte layer, solid electrolytic capacitors are poor at repairing defects in the dielectric oxide film, and there is a risk of increased leakage current. Therefore, so-called hybrid-type solid electrolytic capacitors, in which a solid electrolyte layer is formed on a capacitor element in which a pair of electrode foils are opposed to each other, and the gaps in the capacitor element are impregnated with an electrolytic solution, have attracted attention.

[0005] The solid electrolyte layer is formed by immersing a capacitor element having a pair of electrode foils facing each other in a liquid composition containing a conductive polymer. When the capacitor element is immersed in the liquid composition, the conductive polymer adheres to the capacitor element to form a solid electrolyte layer. The capacitor element with the solid electrolyte layer formed thereon is further impregnated with an electrolyte solution, and the capacitor element impregnated with the electrolyte solution is housed in an exterior case. A sealer having an elastomer layer such as ethylene propylene rubber or butyl rubber is inserted into the opening of the exterior case to seal the inside.

[0006] The acidity of a liquid composition containing a dopant, which is an acid compound, is high. For this reason, it has been pointed out that the electrode foil of a solid electrolytic capacitor may corrode. In response to this problem, a solid electrolytic capacitor containing an alkaline component in a solid electrolyte layer has been proposed (see, for example, Patent Document 1). Specifically, an anode body is immersed in a liquid composition containing a conductive polymer, a polyanion, an alkaline component, and a solvent, or the liquid composition is applied or dropped onto the anode body, and then the solvent of the liquid composition is removed through one or more drying steps. Ammonia is preferably proposed as the alkaline component. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2018 / 123255 Summary of the Invention [Problem to be solved by the invention]

[0008] When solid electrolytic capacitors were made using a liquid composition containing ammonia, the seal cracked and the capacitance decreased in high temperature environments such as 150°C or 180°C. When this phenomenon was investigated, it was hypothesized that when the solvent in the liquid composition was removed by drying, a large amount of ammonia, which has a low boiling point, also evaporated, making it impossible to maintain a neutral state within the capacitor element.

[0009] However, ammonia is useful from the viewpoint of improving voltage resistance characteristics and suppressing an increase in ESR in high-temperature environments, and there are also compounds useful for solid electrolytic capacitors among the volatile alkaline components that are easily evaporated during the process of removing the solvent from the liquid composition, making it difficult to replace it with anything else.

[0010] The present invention has been proposed to solve the above-mentioned problems, and an object of the present invention is to provide a conductive polymer dispersion in which conductive polymer particles or powder are dispersed, which maintains the effect of suppressing an ESR increase and is resistant to a decrease in capacitance, a method for producing this conductive polymer dispersion, a solid electrolytic capacitor made from this conductive polymer dispersion, and a method for producing this solid electrolytic capacitor. [Means for solving the problem]

[0011] In order to solve the above problems, the conductive polymer dispersion of the present invention is a conductive polymer dispersion for forming a solid electrolyte layer in a capacitor element having a pair of electrode foils facing each other, and is characterized in that it contains at least a solvent, a conductive polymer, and an alkaline component, and that the alkaline component contains both a volatile alkaline component and a non-volatile alkaline component.

[0012] The volatile alkali component may have a boiling point of −30° C. or lower, and the non-volatile alkali component may have a boiling point of 1000° C. or higher.

[0013] The volatile alkaline component may be ammonia, and the non-volatile alkaline component may be one or more selected from the group consisting of sodium hydroxide, potassium hydroxide, and calcium hydroxide.

[0014] The molar ratio of the volatile alkali component (A) to the non-volatile alkali component (B) may be in the range of A:B=2:8 to 8:2.

[0015] In addition, in order to solve the above-mentioned problems, the solid electrolytic capacitor of the present invention comprises a capacitor element having a pair of electrode foils facing each other, and an electrolyte layer formed within the capacitor element and containing a solid electrolyte layer and an electrolyte solution, wherein the solid electrolyte layer contains both a volatile alkaline component and a non-volatile alkaline component.

[0016] The electrolytic solution may contain at least glycols as a solvent.

[0017] In addition, in order to solve the above-mentioned problems, the method for manufacturing a solid electrolytic capacitor of the present invention includes a dispersion preparation step of mixing at least a solvent, a conductive polymer, and an alkaline component to prepare a conductive polymer dispersion solution, an attachment step of using the conductive polymer dispersion solution to attach a conductive polymer to a capacitor element having a pair of electrode foils facing each other, a drying step of drying the capacitor element that has undergone the attachment step, and an impregnation step of impregnating an electrolyte into the capacitor element that has undergone the drying step, wherein in the dispersion preparation step, both a volatile alkaline component and a non-volatile alkaline component are added to the conductive polymer dispersion solution as the alkaline component.

[0018] In the drying step, the capacitor element is exposed to a temperature environment equal to or higher than the boiling points of the solvent and the volatile alkaline component and lower than the boiling point of the non-volatile alkaline component. Effect of the Invention

[0019] According to the present invention, it is possible to suppress the deterioration of the sealing member and the decrease in capacitance which are caused by the high acidity of the conductive polymer dispersion liquid. [Brief description of the drawings]

[0020] [Figure 1] 1 is a graph showing the relationship between the molar concentration of ammonia relative to the total of volatile alkaline components and non-volatile alkaline components and ΔCap. [Diagram 2] 1 is a graph showing the relationship between the molar concentration of sodium hydroxide relative to the total of volatile alkali components and non-volatile alkali components and ΔESR. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] (Overall composition) The conductive polymer dispersion and the solid electrolytic capacitor according to the embodiment of the present invention will be described below. The solid electrolytic capacitor is a passive element that stores and discharges electric charge by electrostatic capacitance, and is a so-called hybrid type solid electrolytic capacitor that uses a solid electrolyte layer and an electrolytic solution in combination. Hereinafter, the hybrid type solid electrolytic capacitor will be simply called a solid electrolytic capacitor. The solid electrolytic capacitor has, for example, a wound type or a laminated type shape. In this embodiment, the solid electrolytic capacitor of the present invention will be described by taking a wound type as an example, but the solid electrolytic capacitor of the present invention is not limited to this, and is not limited to other embodiments described.

[0022] A wound-type solid electrolytic capacitor has a cylindrical capacitor element. The capacitor element is inserted into a cylindrical exterior case with a bottom. A sealing body having an elastomer layer such as ethylene propylene rubber or butyl rubber is attached to the open end of the exterior case, and the open end is sealed by crimping. The capacitor element includes a pair of electrode foils separated into an anode side and a cathode side, a separator, and an electrolyte layer, the pair of electrode foils being wound with the separator interposed therebetween, and the electrolyte layer being formed between the pair of electrode foils. A dielectric oxide film is formed on the surface of the electrode foil on the anode side. An anode lead and a cathode lead are connected to each of the pair of electrode foils, and the anode lead and the cathode lead are pulled out from the sealing rubber.

[0023] The electrolyte layer comprises a solid electrolyte layer and an electrolyte solution. The solid electrolyte layer is formed so as to cover at least a part of the dielectric oxide film layer on the surface of the anode foil. The electrolyte solution is filled in the voids of the capacitor element on which the solid electrolyte layer is formed. The solid electrolyte layer contains a conductive polymer, and is formed by immersing the capacitor element in a conductive polymer dispersion liquid and drying it. The conductive polymer dispersion liquid is a liquid in which particles or powder of a conductive polymer are dispersed, and the conductive polymer adheres to the capacitor element as a solid electrolyte layer by immersing the capacitor element in the conductive polymer dispersion liquid. The solvent of the conductive polymer dispersion liquid is removed by drying the capacitor element. The capacitor element on which the solid electrolyte layer is formed is immersed in the electrolyte solution, thereby impregnating the capacitor element.

[0024] (Conductive polymer dispersion) The conductive polymer in the conductive polymer dispersion is a doped conjugated polymer, which is obtained by chemically oxidizing or electrolytically oxidizing a monomer or its derivative having a π-conjugated double bond. By performing a doping reaction on a conjugated polymer, the conductive polymer exhibits high conductivity. That is, conductivity is exhibited by adding a small amount of a dopant, such as an acceptor that easily accepts electrons or a donor that easily gives electrons, to a conjugated polymer. When an acceptor or donor is added to a conjugated polymer, in the case of an acceptor, π electrons are extracted from the conjugated polymer to form a negatively charged simple substance (a hole), and in the case of a donor, electrons are supplied to form a negatively charged carrier, which exhibits conductivity.

[0025] The conjugated polymer may be any known polymer without any particular limitation. For example, polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene, polyphenylene, polyphenylenevinylene, polyacene, polythiophenevinylene, etc. These conjugated polymers may be used alone, or in combination of two or more kinds, or may be a copolymer of two or more kinds of monomers.

[0026] Among the above conjugated polymers, preferred are conjugated polymers obtained by polymerizing thiophene or its derivatives, and preferred are conjugated polymers obtained by polymerizing 3,4-ethylenedioxythiophene (i.e., 2,3-dihydrothieno[3,4-b][1,4]dioxine), 3-alkylthiophene, 3-alkoxythiophene, 3-alkyl-4-alkoxythiophene, 3,4-alkylthiophene, 3,4-alkoxythiophene, or derivatives thereof. As the thiophene derivative, a compound selected from thiophenes having substituents at the 3rd and 4th positions is preferred, and the substituents at the 3rd and 4th positions of the thiophene ring may form a ring together with the carbons at the 3rd and 4th positions. The number of carbon atoms of the alkyl group or alkoxy group is preferably 1 to 16.

[0027] In particular, a polymer of 3,4-ethylenedioxythiophene called EDOT, i.e., poly(3,4-ethylenedioxythiophene) called PEDOT, is particularly preferred.Alkyl ethylenedioxythiophene in which an alkyl group is added to 3,4-ethylenedioxythiophene may also be used, such as methylated ethylenedioxythiophene (i.e., 2-methyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine), ethylated ethylenedioxythiophene (i.e., 2-ethyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine), etc.

[0028] The dopant may be any known dopant without any particular limitation. The dopant may be used alone or in combination of two or more. A polymer or monomer may also be used. For example, the dopant may be an inorganic acid such as a polyanion, boric acid, nitric acid, or phosphoric acid, or an organic acid such as acetic acid, oxalic acid, citric acid, tartaric acid, squaric acid, rhodizonic acid, croconic acid, salicylic acid, p-toluenesulfonic acid, 1,2-dihydroxy-3,5-benzenedisulfonic acid, methanesulfonic acid, trifluoromethanesulfonic acid, borodisalicylic acid, bisoxalate borate acid, sulfonylimide acid, dodecylbenzenesulfonic acid, propylnaphthalenesulfonic acid, or butylnaphthalenesulfonic acid.

[0029] Examples of the polyanion include substituted or unsubstituted polyalkylene, substituted or unsubstituted polyalkenylene, substituted or unsubstituted polyimide, substituted or unsubstituted polyamide, and substituted or unsubstituted polyester, and include polymers consisting of only structural units having an anionic group, and polymers consisting of structural units having an anionic group and structural units not having an anionic group.Specific examples of the polyanion include polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacryl sulfonic acid, polymethacryl sulfonic acid, poly(2-acrylamido-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, polyacrylic acid, polymethacrylic acid, and polymaleic acid.The number average molecular weight of the polyanion is 1,000 to 2,000,000, and preferably 10,000 to 500,000. If the number average molecular weight is less than 1,000, the conductivity of the resulting conductive polymer will be insufficient and dispersibility will decrease, which is undesirable, while if the number average molecular weight exceeds 2,000,000, the viscosity of the mixture will increase, which is undesirable.

[0030] This conductive polymer dispersion further contains a volatile alkali component and a hardly volatile alkali component in addition to a solvent and a conductive polymer. The volatile alkali component and the hardly volatile alkali component are neutralizers for the conductive polymer dispersion, the acidity of which increases due to the presence of a dopant, etc. As long as the conductive polymer dispersion contains a volatile alkali component and a hardly volatile alkali component, it may contain two or more types of volatile alkali components or two or more types of hardly volatile alkali components.

[0031] The solvent for the conductive polymer dispersion may be any solvent that disperses conductive polymer particles or powder, such as water, an organic solvent, or a mixture thereof. Examples of the organic solvent include polar solvents, alcohols, esters, hydrocarbons, carbonate compounds, ether compounds, chain ethers, heterocyclic compounds, and nitrile compounds.

[0032] Examples of polar solvents include N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide. Examples of alcohols include methanol, ethanol, propanol, and butanol. Examples of esters include ethyl acetate, propyl acetate, and butyl acetate. Examples of hydrocarbons include hexane, heptane, benzene, toluene, and xylene. Examples of carbonate compounds include ethylene carbonate and propylene carbonate. Examples of ether compounds include dioxane and diethyl ether. Examples of chain ethers include ethylene glycol dialkyl ether, propylene glycol dialkyl ether, polyethylene glycol dialkyl ether, and polypropylene glycol dialkyl ether. Examples of heterocyclic compounds include 3-methyl-2-oxazolidinone. Examples of nitrile compounds include acetonitrile, glutarodinitrile, methoxyacetonitrile, propionitrile, and benzonitrile.

[0033] The volatile alkaline component is an alkaline component having a boiling point lower than the temperature environment in which the capacitor element immersed in the conductive polymer dispersion liquid is placed when the capacitor element is dried. Examples of the volatile alkaline component include alkaline components having a boiling point of -30°C or less, and specifically, ammonia is preferable. Ammonia suppresses an increase in the equivalent series resistance (ESR) of the solid electrolytic capacitor even if the solid electrolytic capacitor is exposed to a high-temperature environment of 150 to 280°C, such as reflow during mounting.

[0034] The non-volatile alkaline component is an alkaline component having a boiling point higher than the temperature environment in which the capacitor element immersed in the conductive polymer dispersion is placed when the capacitor element is dried. The volatile alkaline component may be, for example, an alkaline component having a boiling point of 1000° C. or higher, and specifically, one or more types selected from the group consisting of sodium hydroxide, potassium hydroxide, and calcium hydroxide are used. The volatile alkaline component suppresses deterioration of the sealing body and suppresses a decrease in the capacitance of the solid electrolytic capacitor.

[0035] The molar ratio of the volatile alkaline component to the non-volatile alkaline component, where A is the volatile alkaline component and B is the non-volatile alkaline component, is preferably in the range of A:B=2:8 to 8:2. If the volatile alkaline component exceeds 80 mol% of the total amount of the alkaline components, the capacitance of the solid electrolytic capacitor decreases significantly. On the other hand, if the volatile alkaline component is less than 20 mol% of the total amount of the alkaline components, the ESR increases significantly in a high-temperature environment.

[0036] Furthermore, by adding a volatile alkali component and a non-volatile alkali component, the pH of the conductive polymer dispersion is preferably adjusted to from 2 to 7, more preferably from 2 to 5. By adjusting the pH within this range, deterioration of the sealing member is further suppressed, and a decrease in the capacitance of the solid electrolytic capacitor is further suppressed.

[0037] The conductive polymer dispersion may contain a polyhydric alcohol in addition to the solvent, conductive polymer, volatile alkali component, and non-volatile alkali component. Examples of the polyhydric alcohol include sorbitol, ethylene glycol, diethylene glycol, triethylene glycol, polyoxyethylene glycol, glycerin, polyoxyethylene glycerin, xylitol, erythritol, mannitol, dipentaerythritol, pentaerythritol, and combinations of two or more of these. Since the polyhydric alcohol has a high boiling point, it can remain in the solid electrolyte layer even after the drying process, and the effect of reducing ESR and improving voltage resistance can be obtained.

[0038] Furthermore, the conductive polymer dispersion may contain other compounds. For example, conventional additives such as organic binders, surfactants, antifoaming agents, coupling agents, antioxidants, and ultraviolet absorbers may be added. It is also possible to significantly reduce the ESR by adding additives to the conductive polymer dispersion or by increasing the number of times the conductive polymer dispersion is impregnated into the capacitor element.

[0039] In the dispersion preparation process of the conductive polymer dispersion, for example, a monomer constituting the conductive polymer and an acid or its alkali metal salt that releases a dopant constituting the conductive polymer are added, a supporting electrolyte is added, electrolytic oxidation polymerization is performed while stirring, and then impurities and residual monomers are removed by purification means such as ultrafiltration, cation exchange, and anion exchange. A conductive polymer dispersion is obtained by this dispersion preparation process. The volatile alkali component and the non-volatile alkali component may be added to the conductive polymer dispersion after the impurities and residual monomers have been removed during the dispersion preparation process.

[0040] The supporting electrolyte can be any compound that releases a dopant contained in a conventional conductive polymer, and examples of the supporting electrolyte include inorganic acids such as boric acid, nitric acid, phosphoric acid, tungstophosphoric acid, and molybdophosphoric acid, organic acids such as acetic acid, oxalic acid, citric acid, tartaric acid, squaric acid, rhodizonic acid, croconic acid, and salicylic acid, as well as sulfonic acids such as methanesulfonic acid, dodecylsulfonic acid, trifluoromethanesulfonic acid, p-toluenesulfonic acid, dodecylbenzenesulfonic acid, 1,2-dihydroxy-3,5-benzenedisulfonic acid, naphthalenesulfonic acid, naphthalenedisulfonic acid, propylnaphthalenesulfonic acid, and butylnaphthalenesulfonic acid, and salts thereof. In addition, polycarboxylic acids such as polyacrylic acid, polymethacrylic acid, and polymaleic acid, polysulfonic acids such as polystyrenesulfonic acid and polyvinylsulfonic acid, and salts thereof can also be used as the supporting electrolyte. Furthermore, boron complexes such as borodisalicylic acid, borodioxalic acid, borodimalonic acid, borodisuccinic acid, borodiadipic acid, borodimaleic acid, borodiglycolic acid, borodilactic acid, borodihydroxyisobutyric acid, borodimalic acid, boroditartaric acid, borodicitric acid, borodiphthalic acid, borodihydroxybenzoic acid, borodimandelic acid, and borodibenzyl acid, sulfonylimide acids, and salts thereof can also be used as the supporting electrolyte.

[0041] Examples of the salt include alkali metal salts such as lithium salt, sodium salt, and potassium salt; alkyl ammonium salts such as ammonium salt, ethyl ammonium salt, and butyl ammonium salt; dialkyl ammonium salts such as diethyl ammonium salt and dibutyl ammonium salt; trialkyl ammonium salts such as triethyl ammonium salt and tributyl ammonium salt; and tetraalkyl ammonium salts such as tetraethyl ammonium salt and tetrabutyl ammonium salt.

[0042] The electrolytic oxidation polymerization is carried out by any one of the methods of the constant potential method, the constant current method, and the potential sweep method. In the case of the constant potential method, a potential of 1.0 to 1.5 V with respect to a saturated calomel electrode is suitable, and in the case of the constant current method, a potential of 1 to 10,000 μA / cm 2In the case of a potential sweep method, it is preferable to sweep in the range of 0 to 1.5 V against a saturated calomel electrode at a rate of 5 to 200 mV / sec. There is no strict limit to the polymerization temperature, but it is generally in the range of 10 to 60°C. The polymerization time is generally in the range of 10 minutes to 30 hours.

[0043] In addition, in the dispersion preparation process of the conductive polymer dispersion, for example, a monomer constituting the conductive polymer and an acid or its alkali metal salt releasing a dopant constituting the conductive polymer are added, an oxidizing agent is added, and the mixture is stirred until chemical oxidation polymerization is completed, and then residual monomers and impurities are removed by purification means such as ultrafiltration, cation exchange, and anion exchange. A conductive polymer dispersion is obtained by this dispersion preparation process. The volatile alkali component and the non-volatile alkali component may be added to the conductive polymer dispersion after the residual monomers and impurities have been removed during the dispersion preparation process.

[0044] As the oxidizing agent, trivalent iron salts such as p-toluenesulfonate iron(III), naphthalenesulfonate iron(III), anthraquinonesulfonate iron(III), or peroxodisulfate salts such as peroxodisulfate, ammonium peroxodisulfate, and sodium peroxodisulfate can be used, and a single compound or two or more compounds may be used. In the chemical oxidation polymerization, the polymerization temperature is not strictly limited, but is generally in the range of 10 to 60°C. The polymerization time is generally in the range of 10 minutes to 30 hours.

[0045] In the electrolytic oxidation polymerization and chemical oxidation polymerization, the solvent can be any solvent that can dissolve the desired amount of monomer and supporting electrolyte and does not adversely affect the electrolytic polymerization. For example, the solvent can be water, methanol, ethanol, isopropanol, butanol, ethylene glycol, acetonitrile, butyronitrile, acetone, methyl ethyl ketone, tetrahydrofuran, 1,4-dioxane, γ-butyrolactone, methyl acetate, ethyl acetate, methyl benzoate, ethyl benzoate, ethylene carbonate, propylene carbonate, nitromethane, nitrobenzene, sulfolane, and dimethylsulfolane. These solvents may be used alone or in combination of two or more.

[0046] (Solid electrolytic capacitor) The electrode foils on the anode and cathode sides are long foils made of valve metals such as aluminum, tantalum, niobium, niobium oxide, titanium, hafnium, zirconium, zinc, tungsten, bismuth, and antimony. The purity of the electrode foil on the anode side is preferably 99.9% or more, and that of the electrode foil on the cathode side is preferably 99% or more, but impurities such as silicon, iron, copper, magnesium, and zinc may be included.

[0047] The anode electrode foil has a porous structure on the surface as a sintered body obtained by sintering a valve metal powder or an etched foil obtained by etching a stretched foil. The porous structure is composed of tunnel-like pits, spongy pits, or voids between densely packed powder particles. The porous structure is typically formed by direct current etching or alternating current etching in an acidic aqueous solution containing halogen ions such as hydrochloric acid, or by vapor deposition or sintering metal particles or the like on the core. The cathode electrode foil may also have a porous structure on the surface as necessary.

[0048] The dielectric oxide film layer is a dielectric layer of a solid electrolytic capacitor, and is typically an oxide film formed on the surface layer of the electrode foil on the anode side. If the electrode foil on the anode side is made of aluminum, the dielectric oxide film layer is an aluminum oxide layer obtained by oxidizing the porous structure region. This dielectric oxide film layer is formed by applying a voltage in a solution that does not contain halogen ions, such as an aqueous solution of adipic acid or boric acid. The electrode foil on the cathode side may also be formed with a dielectric oxide film layer as necessary, and may further include a layer made of metal nitride, metal carbide, or metal carbonitride formed by vapor deposition, or may include carbon on the surface. The dimensions of the anode foil and cathode foil can be set arbitrarily according to the specifications of the solid electrolytic capacitor to be manufactured.

[0049] Examples of the separator include cellulose papers such as kraft, Manila hemp, esparto, hemp, and rayon, and mixed papers thereof; polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and derivatives thereof; polytetrafluoroethylene-based resins, polyvinylidene fluoride-based resins, vinylon-based resins, polyamide-based resins such as aliphatic polyamides, semi-aromatic polyamides, and fully aromatic polyamides; polyimide-based resins, polyethylene resins, polypropylene resins, trimethylpentene resins, polyphenylene sulfide resins, acrylic resins, and polyvinyl alcohol resins. These resins can be used alone or in combination.

[0050] The separator separates the anode and cathode electrode foils to prevent shorting between them, and also holds the solid electrolyte layer between the electrode foils. If the shape of the solid electrolyte layer can be maintained by itself and the cathode and anode electrode foils can be isolated by the solid electrolyte layer, the separator can be eliminated from the solid electrolytic capacitor.

[0051] A capacitor element is produced by winding the pair of electrode foils with a separator interposed therebetween. The separator is overlapped so that one end of the separator protrudes beyond one end of the pair of electrode foils, and the layer of the pair of electrode foils, cathode foil, and separator is wound by first winding the protruding separator to create a winding core, and then winding the winding core as a winding shaft. After that, a solid electrolyte layer is formed on the capacitor element, and the electrolyte is impregnated.

[0052] The solid electrolyte layer contains the conductive polymer contained in the conductive polymer dispersion, a volatile alkaline component, a non-volatile alkaline component, or an additive such as a polyhydric alcohol in addition to these, and adheres closely to the dielectric oxide film of the electrode foil on the anode side to become a true cathode. This solid electrolyte layer is formed by immersing a capacitor element in the conductive polymer dispersion and attaching the conductive polymer to the dielectric oxide film layer. In the conductive polymer attachment step, a decompression treatment or a pressurization treatment may be performed as necessary to promote impregnation of the conductive polymer into the capacitor element. This attachment step may be repeated multiple times.

[0053] In addition to immersion, the conductive polymer dispersion liquid may be impregnated into the capacitor element by drop application, spray application, etc. Furthermore, instead of the entire capacitor element, the anode side electrode foil and the cathode side electrode foil may be immersed in the conductive polymer dispersion liquid, or the conductive polymer dispersion liquid may be applied dropwise or sprayed onto the anode side electrode foil and the cathode side electrode foil before assembling the capacitor element.

[0054] The capacitor element that has been through the impregnation process is dried to remove the solvent from the conductive polymer dispersion. In the drying process, the capacitor element is exposed to a temperature environment of, for example, 80°C to 200°C for 3 minutes to 180 minutes. This drying process may be repeated multiple times. The capacitor element may be dried in a reduced pressure environment, for example, at a pressure of 5 kPa to 100 kPa.

[0055] The electrolytic solution is impregnated into the capacitor element after the conductive polymer adhesion step and the drying step. This electrolytic solution is responsible for at least the repairing action of the dielectric oxide film. In the electrolytic solution, the solvent is preferably glycol-based. When the solvent of the electrolytic solution is glycol-based and the conductive polymer dispersion contains both a volatile alkaline component and a non-volatile alkaline component, the deterioration of the sealing body in a high-temperature environment can be effectively suppressed, and the decrease in the electrostatic capacitance can also be effectively suppressed.

[0056] The glycol-based solvent is a dihydric alcohol in which two different carbon atoms in a chain aliphatic hydrocarbon or a cyclic aliphatic hydrocarbon are substituted with an OH group. For example, the glycol-based solvent may be ethylene glycol, propylene glycol, diethylene glycol, glycerin, polyethylene glycol, or polyoxyethylene glycerin. The electrolyte may contain one or more selected from the glycol-based solvents as a solvent. In addition, as long as the electrolyte contains a glycol-based solvent, the electrolyte may contain a solvent other than the glycol-based solvent.

[0057] The electrolyte includes an anion component and a cation component. The electrolyte can be used without any particular limitation, and is typically a salt of an organic acid, a salt of an inorganic acid, or a salt of a complex compound of an organic acid and an inorganic acid, and is used alone or in combination of two or more. An acid that becomes an anion and a base that becomes a cation may be added separately to the liquid.

[0058] Examples of organic acids that can be anion components include carboxylic acids such as oxalic acid, succinic acid, glutaric acid, pimelic acid, suberic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, maleic acid, adipic acid, benzoic acid, toluic acid, enanthic acid, malonic acid, 1,6-decanedicarboxylic acid, 1,7-octanedicarboxylic acid, azelaic acid, resorcylic acid, phloroglucinic acid, gallic acid, gentisic acid, protocatechuic acid, pyrocatechuic acid, trimellitic acid, and pyromellitic acid, as well as phenols and sulfonic acids. Examples of inorganic acids include boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, carbonic acid, and silicic acid. Examples of composite compounds of organic acids and inorganic acids include borodisalicylic acid, borodioxalic acid, borodiglycolic acid, borodimalonic acid, borodisuccinic acid, borodiadipic acid, borodiazelaic acid, borodibenzoic acid, borodimaleic acid, borodilactic acid, borodimalic acid, boroditartaric acid, borodicitric acid, borodiphthalic acid, borodi(2-hydroxy)isobutyric acid, borodiresorcylic acid, borodimethylsalicylic acid, borodinaphthoic acid, borodimandelic acid, and borodi(3-hydroxy)propionic acid.

[0059] In addition, examples of at least one salt of an organic acid, an inorganic acid, and a complex compound of an organic acid and an inorganic acid include ammonium salt, quaternary ammonium salt, quaternary amidinium salt, amine salt, sodium salt, potassium salt, etc. Examples of quaternary ammonium ions of quaternary ammonium salts include tetramethylammonium, triethylmethylammonium, tetraethylammonium, etc. Examples of quaternary amidinium salts include ethyldimethylimidazolinium, tetramethylimidazolinium, etc. Examples of amine salts include salts of primary amines, secondary amines, and tertiary amines. Examples of primary amines include methylamine, ethylamine, propylamine, etc., examples of secondary amines include dimethylamine, diethylamine, ethylmethylamine, dibutylamine, etc., and examples of tertiary amines include trimethylamine, triethylamine, tributylamine, ethyldimethylamine, ethyldiisopropylamine, etc.

[0060] Furthermore, other additives can be added to the electrolyte. Examples of additives include complex compounds of boric acid and polysaccharides (mannitol, sorbitol, etc.), complex compounds of boric acid and polyhydric alcohols, boric acid esters, nitro compounds (o-nitrobenzoic acid, m-nitrobenzoic acid, p-nitrobenzoic acid, o-nitrophenol, m-nitrophenol, p-nitrophenol, p-nitrobenzyl alcohol, etc.), and phosphoric acid esters. These may be used alone or in combination of two or more.

[0061] The amount of additive is not particularly limited, but it is preferable to add an amount that does not deteriorate the characteristics of the solid electrolytic capacitor, for example, 60 wt% or less in the liquid. Among the above additives, it is preferable to add a complex compound of boric acid and polyhydric alcohol for the purpose of improving the withstand voltage, or to add a nitro compound for the purpose of absorbing gas in the capacitor.

[0062] The electrolyte is filled into the voids of the capacitor element having the solid electrolyte layer formed thereon in an impregnation step after the formation of the solid electrolyte layer. The electrolyte may be impregnated to such an extent that the solid electrolyte layer swells. In the impregnation step, a depressurization treatment or a pressurization treatment may be performed as necessary. EXAMPLES

[0063] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0064] Conductive polymer dispersions of Examples 1 to 4 and Comparative Examples 1 and 2 were prepared by varying the molar ratio of the volatile alkaline component to the non-volatile alkaline component, and solid electrolytic capacitors were produced using each conductive polymer dispersion.

[0065] First, water was used as the solvent to prepare the conductive polymer dispersion. Powder of polyethylenedioxythiophene (PEDOT) doped with polystyrene sulfonate (PSS) (PEDOT / PSS) was added to the water, and both a volatile alkali component and a non-volatile alkali component were added and dissolved in the water. Ammonia (NH3) was used as the volatile alkali component, and sodium hydroxide (NaOH) was used as the non-volatile alkali component.

[0066] In Examples 1 to 4 and Comparative Examples 1 and 2, the ratio of polymer added to water and the ratio of alkaline component added are the same, and the stirring method and conditions are also the same. However, Examples 1 to 4 and Comparative Examples 1 and 2 differ in the molar ratio of the volatile alkaline component and the non-volatile alkaline component added to the conductive polymer dispersion. Table 1 below shows the molar concentrations of ammonia and sodium hydroxide relative to the total alkaline components, which are the combined volatile alkaline component and non-volatile alkaline component added to the conductive polymer dispersion. (Table 1) TIFF2025032011000002.tif50161

[0067] A capacitor element in which a solid electrolyte layer is formed by this conductive polymer dispersion liquid was commonly produced in each Example and Comparative Example as follows. That is, the electrode foils on the anode and cathode sides were aluminum foils, which were enlarged by etching, and a dielectric oxide film was formed on the electrode foil on the anode side by chemical conversion treatment. Lead wires were connected to each of the electrode foils on the anode and cathode sides, and the electrode foils on the anode side and cathode side were wound facing each other with a manila separator interposed therebetween. In this way, a capacitor element was produced. This capacitor element was repaired by immersing it in an aqueous solution of ammonium dihydrogen phosphate for 10 minutes.

[0068] This capacitor element was immersed in the conductive polymer dispersion liquid of each Example and Comparative Example. After the capacitor element was pulled out of the conductive polymer dispersion liquid, it was dried at 150° C. for 30 minutes. The immersion and drying were repeated twice. As a result, a solid electrolyte layer was formed on the capacitor element.

[0069] In addition, an electrolyte solution containing ethylene glycol as a solvent and ammonium azelaate as a solute was prepared for each of the examples and comparative examples. The electrolyte solution was then impregnated into the capacitor element having the solid electrolyte layer formed thereon. The capacitor element was then inserted into an aluminum, bottomed, cylindrical exterior case, and a sealing rubber made of butyl rubber was attached to the open end, followed by crimping to seal the capacitor element.

[0070] Each solid electrolytic capacitor was subjected to aging treatment by applying a voltage. The rated voltage of each solid electrolytic capacitor was 35V and the rated capacity was 47μF. The solid electrolytic capacitors of Examples 1 to 4 and Comparative Examples 1 and 2 were exposed to a high temperature environment of 180℃. Then, the ESR before exposure to the high temperature environment, i.e., before thermal stress loading, and the ESR after exposure to the high temperature environment for 150 hours were measured, and the change rate ΔESR of these ESRs was calculated. In addition, the capacitance before thermal stress loading and the capacitance after exposure to the high temperature environment for 323 hours were measured, and the change rate ΔCap of these capacitances was measured. The ESR was measured by passing an AC current of 100kHz through the solid electrolytic capacitor, and the capacitance was measured by passing an AC current of 120Hz through the solid electrolytic capacitor.

[0071] The measurement results for each of the examples and comparative examples are shown in Table 2 below. (Table 2) TIFF2025032011000003.tif59164

[0072] FIG. 1 is a graph showing the relationship between the ammonia concentration and the rate of change in capacitance ΔCap for the total amount of volatile alkali components and non-volatile alkali components based on Table 2 above, and FIG. 2 is a graph showing the relationship between the sodium hydroxide concentration and the rate of change in ESR ΔESR for the total amount of volatile alkali components and non-volatile alkali components based on Table 2 above.

[0073] As shown in Table 2 and Figure 1, the solid electrolytic capacitor of Comparative Example 1, in which the solid electrolyte layer was formed from a conductive polymer dispersion liquid to which only a volatile alkaline component, ammonia, was added, showed a significant decrease in capacitance when exposed to a high-temperature environment. Also, as shown in Table 2 and Figure 2, the solid electrolytic capacitor of Comparative Example 2, in which the solid electrolyte layer was formed from a conductive polymer dispersion liquid to which only a non-volatile alkaline component, sodium hydroxide, was added, showed a significant increase in ESR when exposed to a high-temperature environment.

[0074] On the other hand, as shown in Table 2 and Figs. 1 and 2, it was confirmed that the solid electrolytic capacitors of Examples 1 to 4 in which the solid electrolyte layer was formed from the conductive polymer dispersion liquid to which both the volatile alkaline component, ammonia, and the non-volatile alkaline component, sodium hydroxide, were added, maintained their capacitance and ESR well even when exposed to a high-temperature environment.

Claims

1. A method for producing a conductive polymer dispersion for forming a solid electrolyte layer of an electrolytic capacitor, comprising the steps of: The method includes a mixing step of mixing at least a solvent, a conductive polymer, an alkali component, and a polyhydric alcohol, In the mixing step, both a volatile alkali component and a non-volatile alkali component are mixed as the alkali component; A method for producing a conductive polymer dispersion, comprising:

2. The volatile alkali component has a boiling point of −30° C. or lower, The low-volatility alkali component has a boiling point of 1000° C. or higher; 2. A method for producing the conductive polymer dispersion according to claim 1,

3. The volatile alkaline component is ammonia, the low-volatility alkali component is at least one selected from the group consisting of sodium hydroxide, potassium hydroxide, and calcium hydroxide; 3. The method for producing the conductive polymer dispersion according to claim 1 or 2,

4. The molar ratio of the volatile alkali component (A) to the non-volatile alkali component (B) is in the range of A:B=2:8 to 8:2; 4. The method for producing the conductive polymer dispersion according to claim 1, wherein

5. The capacitor element includes an electrolyte layer including a solid electrolyte layer and an electrolyte solution. the solid electrolyte layer contains both a volatile alkaline component and a hardly-volatile alkaline component, and a polyhydric alcohol; A solid electrolytic capacitor characterized by:

6. The electrolyte contains at least a glycol as a solvent; 6. The solid electrolytic capacitor according to claim 5,

7. a dispersion liquid preparation step of preparing a conductive polymer dispersion liquid by mixing at least a solvent, a conductive polymer, an alkali component, and a polyhydric alcohol; a step of adhering a conductive polymer to a capacitor element using the conductive polymer dispersion; a drying step of drying the capacitor element that has been subjected to the adhering step; an impregnation step of impregnating the capacitor element having been subjected to the drying step with an electrolyte; Including, In the dispersion preparation step, both a volatile alkali component and a non-volatile alkali component are added to the conductive polymer dispersion as the alkali component; A method for producing a solid electrolytic capacitor comprising the steps of:

8. In the drying step, the capacitor element is exposed to a temperature environment that is equal to or higher than the boiling points of the solvent and the volatile alkaline component and lower than the boiling point of the non-volatile alkaline component; 8. The method for producing a solid electrolytic capacitor according to claim 7,

9. A conductive polymer dispersion liquid for forming a solid electrolyte layer in a capacitor element of an electrolytic capacitor, The composition contains at least a solvent, a conductive polymer, a polyhydric alcohol, and an alkaline component, The alkaline component contains both a volatile alkaline component and a non-volatile alkaline component; The conductive polymer dispersion liquid is characterized by:

Citation Information

Patent Citations

  • Solid electrolytic capacitor and manufacturing method thereof

    JP2012114249A

  • Electrolytic capacitor and method for manufacturing same

    WO2018123255A1

  • Solid electrolytic capacitor

    WO2020059672A1